Analysis of Service Quality on Visitor Satisfaction at California Cialam Jaya Agrotourism Site, Tanea Village, Konda Subdistrict, South Konawe Regency - Sumiyati; Gafarudin, Abdul; Sadimantara, Fahria Nadiryati (International Journal of Technology and Education Research, 2026)
This study aims to analyze the quality of service on visitor satisfaction at California Cialam Jaya Agrotourism, Tanea Village, Konda District, South Konawe Regency. This study uses a quantitative descriptive method with the Importance Performance Analysis (IPA) approach. The research sample consisted of 44 respondents obtained through accidental sampling techniques. Data were collected through distributing questionnaires that measured five dimensions of service quality, namely: tangible (physical evidence), reliability, responsiveness, assurance, and empathy. The results of the study indicate that the level of satisfaction with the performance of the quality of service of Agowisata California Cialam Jaya is in the "good" category with an average of 89.90% because it shows that most visitors are satisfied with the quality of service provided, but there are still several attributes and there are service attributes that are included in Quadrant III in the Cartesian Diagram which show low priority both in terms of importance and performance. This indicates that although these attributes are not the main concern of visitors, the quality of service still needs to be improved gradually to prevent potential dissatisfaction in the future and maintain consistency in improving the quality of service as a whole